Inorganic Janus nanosheets bearing two types of covalently bound organophosphonate groups via regioselective surface modification of K4Nb6O17·3H2O. Issue 45 (21st May 2018) - Suzuki, Ryoko; Sudo, Mitsuhito; Hirano, Megumi; Idota, Naokazu; Kunitake, Masashi; Nishimi, Taisei; Sugahara, Yoshiyuki
Abstract : Inorganic Janus nanosheets bearing covalently bound were successfully prepared from K4 Nb6 O17 ·3H2 O and two organophosphonic acid. Abstract : Janus nanosheets were prepared from K4 Nb6 O17 ·3H2 O by modifying surfaces of their two distinct interlayers in a regioselective and sequential manner and subsequent exfoliation. The surface properties of nanosheets were investigated by phase atomic force microscopy imaging and two types of surfaces were discriminated, indicating that Janus nanosheets were successfully prepared.